Expansion of Perceptual Body Maps Near – But Not Across – The Wrist - Longo, Matthew R. (Frontiers in Human Neuroscience, 2017)
Perceiving the external spatial location of touch requires that tactile information about the stimulus location on the skin be integrated with proprioceptive information about the location of the body in external space, a process called tactile spatial remapping. Recent results have suggested that this process relies on a distorted representation of the hand. Here, I investigated whether similar distortions are also found on the forearm and how they are affected by the presence of the wrist joint, which forms a categorical, segmental boundary between the hand and the arm. Participants used a baton to judge the perceived location of touches applied to their left hand or forearm. Similar distortions were apparent on both body parts, with overestimation of distances in the medio-lateral axis compared to the proximo-distal axis. There was no perceptual expansion of distances that crossed the wrist boundary. However, there was increased overestimation of distances near the wrist in the medio-lateral orientation. These results replicate recent findings of a distorted representation of the hand underlying tactile spatial remapping, and show that this effect is not idiosyncratic to the hand, but also affects the forearm. These distortions may be a general characteristic of the mental representation of the arms.